Human and global identities: different prototypical meanings of all-inclusive identities - Carmona, M. (2020)
The impact of identities encompassing all human beings (e.g., human and/or global identities) on intergroup relations is complex, with studies showing mostly positive (e.g., less dehumanization), but also negative (e.g., deflected responsibility for harm behavior), effects. However, different labels and measures have been used to examine the effects of these all-inclusive superordinate identities, without a systematic empirical examination of the extent to which they overlap or differ in their sociopsychological prototypical content. This study examined whether different labels activate the same contents in laypeople's conceptualization. Two hundred and forty-eight participants openly described one of six labels: “All humans everywhere”; “People all over the world”; “People from different countries around the world”; “Global citizens”; “Citizens of the world”; and “Members of world community.” Results from quantitative content analyses showed that the different labels activated different thematic attributes, representing differences in their core prototypical meaning. We propose that a general distinction should be made between labels that define membership based on human attributes (e.g., biological attributes) and those that evoke attributes characteristic of membership in a global political community (e.g., attitudinal attributes), as their effect on intergroup relations may vary accordingly.